2010
DOI: 10.1080/00288306.2010.526545
|View full text |Cite
|
Sign up to set email alerts
|

Crustal seismic reflection profile across the alpine fault and coastal plain at Whataroa, South Island

Abstract: Crustal seismic reflection data recorded across the Alpine Fault and coastal plain at Whataroa in 1998 are used to derive shallow (4 seconds two-way time or s twt) and deep (14 s twt) seismic reflection images and a simple refraction model. A single 25 km long, 636 channel receiver array recorded energy from 50 kg shots fired at 1 km intervals with intervening shots of 2.5 kg at about 300 m intervals along the profile. Record quality varied from good to poor. Across the Alpine Fault, basement lies at about 300… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(54 citation statements)
references
References 21 publications
9
45
0
Order By: Relevance
“…For the larger‐scale Whataroa98 P wave model (Figure b) there have been previous analyses using ray tracing of first break refraction arrivals by Davey []. Comparing the final P wave velocity model derived for the Whataroa98 data set in this study with the results obtained by Davey [], Figure shows their compatibility.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…For the larger‐scale Whataroa98 P wave model (Figure b) there have been previous analyses using ray tracing of first break refraction arrivals by Davey []. Comparing the final P wave velocity model derived for the Whataroa98 data set in this study with the results obtained by Davey [], Figure shows their compatibility.…”
Section: Discussionsupporting
confidence: 72%
“…The final velocity model obtained by interpolation and extrapolation of the Whataroa98 data set result from Figure b is overlain by contour lines derived by Davey []. In principal, the shown P wave velocity structures coincide and reveal a deeper sedimentary basin in the northwest and a shallow basement in the southeast.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…They conclude that seismic anisotropy is a pervasive feature throughout much of the South Island crust, where many faults exist. This strong anisotropy may explain, for example, why guided wave studies of the Alpine Fault have indicated a 10-40% velocity reduction, whereas refraction studies have implied a much smaller velocity reduction of 4-16% and the fault has been imaged as a weak reflector [Eccles et al, 2015;Davey, 2010;Eberhart-Phillips and Bannister, 2002].…”
Section: 1002/2017gl073726mentioning
confidence: 99%